Clinical and Epidemiological Profile of Patients with Ewings Sarcoma (Global Journal of Medical Research, 2023)
Introduction Understanding that cancer is a pathology that is challenging to detect treat and comprehend is what makes the study of cancer so important The goal of this case study is to show how a 20-year-old woman was affected by a variety of factors and symptoms that when combined raised suspicion of Ewing s sarcoma the second most common primary tumor in children and young adults Ewing s sarcoma has the characteristics of being an aggressive malignancy originating in the bones
Keywords: ewing's sarcoma; chest wall tumor; oncology